2014
DOI: 10.12659/pjr.890209
|View full text |Cite
|
Sign up to set email alerts
|

Myositis ossificans mimicking sarcoma, the importance of diagnostic imaging – case report

Abstract: SummaryBackgroundMyositis ossificans is localized inflammatory process affecting skeletal muscles. Very rarely it can affect one of the neck muscles and present as a neck tumor, it can be misdiagnosed as the clinical, radiological and histological examinations can mimic a sarcoma.Case ReportWe report a 29 year old female patient with neck tumor suspected to be a sarcoma who underwent full diagnostics imaging and open bipsy with histopatological examination, afterwards surgical excision was performed.Conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The radiologic findings of early MO depended on the site and extent of its evolution. According to past reports and our study, the typical MRI features of early MO are as follows: (1) the intramuscular lesion shows as isointense or slightly hyperintense in T1-WI and hyperintense in T2-WI [ 3 , 4 , 8 , 14 , 15 ], (2) the margin of the lesion may be ill-defined, with extensive surrounding muscle edema [ 3 , 4 , 16 ], and (3) the lesion appears diffusely or peripherally enhanced after MRI contrast enhancement [ 3 , 4 , 17 ]. Sometimes, periostitis, reactive joint effusions, and bone marrow edema may appear in acute conditions [ 3 ].…”
Section: Discussionmentioning
confidence: 65%
“…The radiologic findings of early MO depended on the site and extent of its evolution. According to past reports and our study, the typical MRI features of early MO are as follows: (1) the intramuscular lesion shows as isointense or slightly hyperintense in T1-WI and hyperintense in T2-WI [ 3 , 4 , 8 , 14 , 15 ], (2) the margin of the lesion may be ill-defined, with extensive surrounding muscle edema [ 3 , 4 , 16 ], and (3) the lesion appears diffusely or peripherally enhanced after MRI contrast enhancement [ 3 , 4 , 17 ]. Sometimes, periostitis, reactive joint effusions, and bone marrow edema may appear in acute conditions [ 3 ].…”
Section: Discussionmentioning
confidence: 65%
“…The chondrocytes of parosteal OS usually show more pleomorphism and occasional binucleation and a lack of regular columnar arrangement and polarity [9]. Myositis ossificans may be grossly similar to parosteal OS, radiographically, however, the ossification pattern of parosteal OS is generally centrally located whereas the ossification pattern of myositis ossificans is peripherally located [10]. In addition, lesions of parosteal OS on MRI are more hypointense both in T1-weighted and T2-weighted images [10].…”
Section: Discussionmentioning
confidence: 99%
“…Myositis ossificans may be grossly similar to parosteal OS, radiographically, however, the ossification pattern of parosteal OS is generally centrally located whereas the ossification pattern of myositis ossificans is peripherally located [10]. In addition, lesions of parosteal OS on MRI are more hypointense both in T1-weighted and T2-weighted images [10]. A high-grade surface OS is another entity that may be confused with parosteal OS.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, it has not been reported previously that CAF contains these fatty signals in calcifications. In other entities such as myositis ossificans, it has been reported that fatty areas resembling the yellow bone marrow, appeared in calcified areas [11] . In diffuse idiopathic skeletal hyperostosis and ossification of the posterior longitudinal ligament, fatty signals can be seen in calcifying lesions on MRI [12] .…”
Section: Discussionmentioning
confidence: 99%